SegWeigh: A mixed‐method approach to segmenting potential contraceptive user groups and meeting Family Planning 2020 goals. (27th March 2015) - Reichwein, Barbara; Wolmarans, Liezel; Nantayi, Lois; Nassali, Faith; Kakinda, Allan; Musumba, Duncan; Nguyen, Thang H.; Baatsen, Pam
Abstract: Objective: To evaluate a low‐cost mixed‐method research tool (SegWeigh) that informs awareness raising and family planning interventions for potential contraceptive users. Methods: A pilot study of SegWeigh was conducted in Uganda and Vietnam between September 3, 2012, and February 21, 2013. User archetypes were produced in four steps by triangulating Demographic and Health Survey (DHS) data; a secondary literature review; family planning service provision data; and primary qualitative investigation. Results: Triangulation of DHS analysis, secondary literature and service data revealed three potential user profiles: Ugandan women wanting to space pregnancies; Ugandan men wanting to limit pregnancies; and unmarried Vietnamese women having infrequent sex. Archetypes were subsequently created of "Kibuuka, " a 52‐year‐old semi‐literate subsistence farmer in rural Uganda, and "Anh, " a 20‐year‐old student in Hanoi, Vietnam. Conclusion: SegWeigh rapidly produced data‐rich "real life" user profiles that might help to tailor family planning interventions.